"Africa for the Africans?" – Mapmaking, Lagos, and the Colonial Archive. (15th June 2020) - Adelusi-Adeluyi, Ademide
Abstract: In early colonial Lagos, struggles over race, place and identity were played out over ownership of land, and ended with the displacement of sections of the indigenous population. "Africa for the Africans" combines texts and maps to narrate the history of 1860s Lagos. This article demonstrates how, with Geographic Information Systems (GIS), European colonial maps can be used to analyze the significance of changing urban spatial relationships in 1860s Lagos. Though much of this analysis employs GIS, it also leans heavily on other tools for making timelines, story maps and vector diagrams. This process of creating digital representations of the past also has pedagogical applications, as these methods can be extended to the classroom for undergraduates learning about African history.